2012
DOI: 10.1080/11250003.2011.623722
|View full text |Cite
|
Sign up to set email alerts
|

Amphibians conservation in Italy: The contribution of the WWF Oases network

Abstract: Amphibians have emerged as a major conservation concern because of the global decline in their numbers in recent decades. Notwithstanding, they are often neglected in conservation planning respects to other less threatened vertebrate groups. In Italy, few studies have analyzed the effectiveness of amphibian protection regimes. The main aim of this paper is to estimate the contribution of the WWF oases network to amphibians conservation in Italy. Moreover, we conducted a prioritization of this network and we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Stokland, ; Gaspar et al ., ). The present study focus on geographic priorities for saproxylic beetles conservation in Italy, where several studies have addressed the effectiveness of protected areas for terrestrial vertebrates only (Maiorano, Falcucci & Boitani, ; Maiorano et al ., ; D'Amen et al ., ; Bombi et al ., 2011 a ). These authors found that existing protected areas are often insufficient to conserve current patterns of biodiversity in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Stokland, ; Gaspar et al ., ). The present study focus on geographic priorities for saproxylic beetles conservation in Italy, where several studies have addressed the effectiveness of protected areas for terrestrial vertebrates only (Maiorano, Falcucci & Boitani, ; Maiorano et al ., ; D'Amen et al ., ; Bombi et al ., 2011 a ). These authors found that existing protected areas are often insufficient to conserve current patterns of biodiversity in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…A coexistence of high herptile diversity and dense human settlements across Europe could be particularly worrying from a conservation biogeography perspective (Araújo, ) and would require increasing efforts for wetland habitat restoration in urbanized landscapes (Scheffers & Paszkowski, ). Herptiles face increasing conservation threats (Stuart et al ., ; Sinervo et al ., ) and are nevertheless neglected compared with other vertebrates (Bombi et al ., ), besides being the object of negative attitudes from people (Ceríaco, ). The broad‐scale species–people correlation could be particularly important for amphibians, as both people and amphibians depend on the availability of freshwater (e.g.…”
Section: Introductionmentioning
confidence: 99%